ANALISIS PENERAPAN PRINSIP GOOD GOVERNANCE PADA PELAYANAN PUBLIK DI BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN BULELENG - Aryandono, Komang Kappa Tri; Heryanda, Komang Krisna; Telagawathi , Ni Luh Wayan Sayang (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract. This research aims to analyze the application of good governance principles and develop development strategies to increase the implementation of good governance in public services at the National Unity and Political Agency of Buleleng Regency. The research location is the National Unity and Politics Agency of Buleleng Regency. The subjects in this research were 60 mass organizations. The object of this research is the principles of good governance, public services, National Unity and Politics. The sample in the research used census techniques, namely: 60 officially registered mass organizations and all of them were used as research respondents and 4 elements of public service management. The data collection technique uses questionnaires and interviews which are filled in via Google Form. Data analysis techniques use descriptive analysis and SWOT. The research results show the factors that influence the implementation of good governance: human resources have carried out their duties well, but attention needs to be paid to the attitude of human resources in serving the community and needs to be improved. Community participation has been good in every activity, and the desire to participate and convey aspirations has not been closed Abstrak Penelitian ini bertujuan untuk menganalisis penerapan prinsip good governance serta menyusun strategi pengembangan untuk peningkatan penerapan good governance pada pelayanan publik di Badan Kesatuan Bangsa dan Politik Kabupaten Buleleng. Lokasi penelitian yaitu Badan Kesatuan Bangsa dan Politik Kabupaten Buleleng. Subjek dalam penelitian ini 60 ormas. Objek penelitian ini prinsip good governance, pelayanan publik, Badan Kesatuan Bangsa dan Politik. Sampel pada penelitian menggunakan teknik sensus yaitu: 60 ormas yang resmi terdaftar dan seluruhnya dijadikan responden penelitian dan 4 unsur pengelola pelayanan publik. Teknik pengambilan data menggunakan metode kuisioner dan wawancara yang diisi melalui Google Form. Teknik analisis data menggunakan analisis deskriptif dan SWOT. Hasil penelitan menunjukkan dari faktor yang mempengaruhi pelaksanaan good governance: sumber daya manusia sudah melaksanakan tugas dengan baik namun perlu di perhatikan sikap sumber daya manusia dalam melayani masyarakat serta perlu ditingkatkan. Partisipasi masyarakat sudah baik dalam setiap kegiatan, serta tidak menutup keinginan berpartisipasi, menyampaikan aspirasi.